Abiotic factors structuring habitat use in angel sharks, Squatina squatina - Rogers, Tristan (2017)
The distribution and degree of habitat specialism in endangered shark species is known to compound the risk of extinction (Walker 1998). However, such information is not known of Squatina squatina, despite the critically endangered status of the species (OSPAR commission 2010). As such, this research has used one of the largest online surveys on S. squatina’s distribution to gain such information. Similarly, data on S. squatina’s habitat associations were collected on SCUBA from visual census surveys at two sites in Lanzarote (Canary Islands, Spain), and analysed with T-tests. The online survey produced a number of key areas relating to S. squatina mating or breeding. However, some sites were associated with both mating and breeding, suggesting the presence of a mating site and nursery area in the same location, something which has seldom been observed in other shark species, but which is thought to be crucial information which can lead to more informed decisions and contribute to the conservation of the species (e.g. MPAs, nature reserves, protection plans etc.) (Carrier and Pratt 1998). Results of the visual census surveys suggest that S. squatina has a preference for more complex habitat types (i.e. higher levels of macro algae and loose rock) and a specific range of benthic sediment grade. Furthermore, juvenile S. squatina were found to occur at significantly shallower depths than mature S. squatina, while gravid females were found to occur in waters which were significantly lower in temperature than non-gravid females. This type of habitat information of an endangered shark species also has the potential to contribute to conservation efforts as it can, for example, allow us to better understand why a species may select certain habitats and therefore better decide which elements of a habitat need preserving and protecting (Springer 1967, Sims 2003).